Attitudes of farmers towards irrigation water rationalization practices in some villages of Kafr El-Sheikh Governorate - El-Tantawy, Shady Abdel-Salam Mohamed; Salama, Mona F; Abdullah, Hamza H (Journal of agricultural, environmental and veterinary sciences, 2021)
This research aimed to identify the attitude of farmers towards irrigation water rationalization practices, to determine the correlation between the degree of their attitudes towards those practices and the independent variables studied, and to determine the contribution of each of the studied independent variables related to the moral correlation in the interpretation of the total variation in the degrees of trends of farmers towards irrigation water rationalization practices, and finally to identify the obstacles they face when using these practices from their viewpoint.This research was conducted in Kafr El-Sheikh governorate, as it is one of the governorates that suffer from water deficit. Kafr El-Sheikh and Desouq districts were randomly selected. Then, in the same way, two villages were selected from each district. The selected villages were Al-Khadimiya and Arrimon in the Kafr El-Sheikh district and Sanhur, and Mehalet Diyai in Desouk district. A random sample of 225 respondents was selected. They represent 5% of the total number of farmers in each of the four selected villages. The frequencies, percentages, and average arithmetic, Standard deviation, weighted average score, Pearson correlation coefficient, step-wise correlation, and multiple regression analysis model were used in data analysis and presentation of the results.The results could be summarized as follows:1- 25.3% of the respondents' farmers had a negative attitude, 46.7% of them had a neutral attitude, and 28% of them showed positive attitudes towards irrigation water rationalization practices.2- Combined seven independent variables explained 51% of the total variation in the degree of the researchers ’attitudes towards rationalizing irrigation water practices, which are the respondent’s education, the agricultural land tenure, the degree of exposure to information sources in the field of irrigation water rationalization, the degree of contribution in irrigation extension activities, the degree of neighbors effectiveness, the degree of regeneration, and the number of years of using irrigation water rationalization practices.3- The most important obstacles are facing the respondents' farmers in terms of rationalizing irrigation water practices are: the high costs of lining irrigation ditches, the scarcity of water at the ends of the canals, the high costs of laser leveling.
Keywords: farmers' trends; rationalization practices; irrigation water